Balance of Family Life and Professional Life and Stress Among Caregivers - Ouyi, Badji; Avogan, Yaovi Alexandre (Advances in Social Sciences Research Journal, 2023)
The study in this paper was carried out on the health workers of the CHR-Tsévié in Togo, and involves two main variables: work-life balance and stress at work. The purpose of this paper is to explore the effect of the reconciliation of spheres on stress by using reconciliation measures as a moderating effect. Data were collected from 107 individuals regardless of gender, using a questionnaire. They were then processed using Excel and SPSS. Our results confirm the relationship between work-life balance and stress among the caregivers of the Regional Hospital Center of Tsévié. (r=0.192; p = 0.048 < 0.05). Therefore, we will argue that a better organization in terms of reconciling the two spheres of life (family and professional) will make it possible to reduce the suffering linked to stress among caregivers.